Significance of Murabahah Finance towards the Improvement of Agricultural Productivity in Kano State, Nigeria - Aziz, Ahmad Bashir; Mohammed, Ahmed Ibrahim (Science Publishing Corporation Inc, 2018)
Murabahah finance (mark-up) is an Islamic financial product which engages in sales of a commodity in cash or in credit with a full knowledge and agreement on the cost of a commodity and profit margin by both the buyer and the seller.It explores the Shariah legal justification and it is viable in advancing agricultural output of the most populous state of Nigeria.Equally, the study momentarily revealed the background of Kano state. The state is occupied by agricultural output and agro-allied industrial products that serve as a channel of earning income to the farmers and government prior to the discovery and exploration of oil.The study is intents to poster the significance Murabahah finance towards the improvement of this type of Islamic financial product in order to contribute to the agricultural output of Kano state. This paper aims to put into the development of the 44 Kano state micro finance banks, which are the infant financial institution owned by the state government.It is hoped that the outcome of this research will improve the socioeconomic standard of rural farmers, enhance food supply, agribusiness, and agro allied industries of the state. It is also hoped that the application of Murabahah will attract both local and foreign investors which will lead to the economic growth of Kano state and Nigeria in general. This study employed qualitative research methodology, whereby the data will be extracted from the books, magazines, scholarly articles, and other relevant websites material.